An Ethical Framework for Cost-Effective Medicine: Confronting the Risks in Managed Care - Walter M. Cadette (Levy Economics Institute of Bard College, 1998)
This paper looks at the ethical problems posed by managed care (in particular, at its incentives to physicians to economize on care), and points to a regulatory framework to provide consumer protection. HMO medicine has been effective in controlling once runaway health care costs. But it sets up inevitable conflict between patient care and the financial well-being of the health plan and of its employee or contract physicians. The trend to capitated payments is especially problematic. It relieves the insurer from interfering in medical decision-making as a means of cost-control, but it pits the interests of physicians directly against the interest of patients. Policy makers, the finding is, should not try to micro-manage HMO medicine, which they have done by mandating, for example, minimal hospital stays after childbirth. The real need is for regulatory oversight of financial incentives and disclosure. Health plans ought to be required to disclose the incentives under which their physicians are paid; to provide subscribers with honest information on health care coverage; and to be prohibited from imposing "gag rules" on physicians. Moreover, ERISA ought to be re-cast to hold health plans accountable for errant care decisions, which they are not now in many cases. Purchasing cooperatives, the conclusion also is, would play an especially useful role if managed care continues to take hold as the institutional norm.
Keywords: 330